The last unkillable thing : poems - Pittinos, Emily (Iowa poetry prize., 2021)
""What will be possible / when I'm no longer sorry?" asks the speaker of THE LAST UNKILLABLE THING after the sudden death of a parent. "What do lost daughters burst into?" In this debut collection by Emily Pittinos, the speaker is tasked with relearning the ways of loneliness, family, sex, and wilderness as a person who feels thoroughly and abruptly without. Shaped by both concision and unfolding sequences, THE LAST UNKILLABLE THING is a journey across landscapes of mourning where "in [the] periphery, every shadow / is a new dead thing." The light of these poems takes on the tint of grief, and through that light the speaker reexamines what remains: her changed self, her desire, the midwestern flora, the unyielding snow. Interior and exterior ecologies blur until loss becomes a place of its own, and the only inevitability. "Doesn't it hurt," Pittinos writes, "to be human. I'm so human, I could die.""--